Impact of SCBA size and firefighting work cycle on firefighter functional balance. (May 2018) - Kesler, Richard M.; Deetjen, Grace S.; Bradley, Faith F.; Angelini, Michael J.; Petrucci, Matthew N.; Rosengren, Karl S.; Horn, Gavin P.; Hsiao-Wecksler, Elizabeth T.
Abstract: Slips, trips and falls are leading causes of fireground injuries. A functional balance test (FBT) was used to investigate the effects of self-contained breathing apparatus (SCBA) size and design, plus firefighting work cycle. During the FBT, subjects walked along a narrow platform and turned in defined spaces, with and without an overhead obstacle. Thirty firefighters wore three varying-sized standard SCBAs and a low-profile prototype SCBA during three simulated firefighting work/rest cycles. Firefighters were tested pre- and post-firefighting activity (one bout, two bouts with a 5-min break, or back-to-back bouts with no break). Subjects committed more errors and required longer completion times with larger SCBAs. Use of the prototype SCBA lead to lower times and fewer errors. Performing a second bout of firefighting increased completion time. Firefighters need to consider how SCBA and amount of physical activity on the fireground may influence balance in order to reduce the risk of injury. Highlights: Balance test involved walking a narrow platform and turning in defined spaces. Subjects committed more errors with longer test completion times with larger SCBA. Use of a prototype SCBA lead to improved performance relative to one of similar mass. Completion of multiple bouts of firefighting resulted in increased completion time.